2016
DOI: 10.2147/copd.s103998
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators influencing self-management among COPD patients: a mixed methods exploration in primary and affiliated specialist care

Abstract: Self-management is becoming increasingly important in COPD health care although it remains difficult to embed self-management into routine clinical care. The implementation of self-management is understood as a complex interaction at the level of patient, health care provider (HCP), and health system. Nonetheless there is still a poor understanding of the barriers and effective facilitators. Comprehension of these determinants can have significant implications in optimizing self-management implementation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…28,29 We found the results of the needs assessment study were not only useful for guiding the development of our proposed HL tool but also helped to identify possible gaps in respiratory disease management research. Our participants reported several barriers for engaging in selfmanagement practices, which are consistent with those found in the literature; [40][41][42][43] including improper communication with health-care providers and difficulty accessing and understanding health-related information. Utilizing medical jargon and unfamiliar terminology (in verbal or written communication) by health-care providers, in "I don't know that I would talk about diet, and mentioned exercise but not in specifics about I want to do this, so can we come up with a plan for me to be able to stabilize me being active?"…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…28,29 We found the results of the needs assessment study were not only useful for guiding the development of our proposed HL tool but also helped to identify possible gaps in respiratory disease management research. Our participants reported several barriers for engaging in selfmanagement practices, which are consistent with those found in the literature; [40][41][42][43] including improper communication with health-care providers and difficulty accessing and understanding health-related information. Utilizing medical jargon and unfamiliar terminology (in verbal or written communication) by health-care providers, in "I don't know that I would talk about diet, and mentioned exercise but not in specifics about I want to do this, so can we come up with a plan for me to be able to stabilize me being active?"…”
Section: Discussionsupporting
confidence: 87%
“…-Asthma addition to patients' failure to communicate their questions or concerns, were inevitably reported by different studies as major obstacles to appropriate engagement in diseasemanagement process. 41,42,[44][45][46] Around 70% of patients in our study indicated they knew their limitations such as lack of transportation, lack of speaking the same language that the physician, lack of education in their disease, etc., however, many of them also stated they felt reluctant to express their concerns or ask questions, due to the short visit time or attitude of the care provider. In addition, more than half of our study participants reported having low confidence in their health-care provider's interest to listen or respond their questions, preventing proper communication with their care provider.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, receiving personal attention in an atmosphere in which there is enough time taken for the person, apart from their illness, was stressed as important by COPD patients during consultations in a Dutch outpatient clinic and at their general practitioner's surgery. Moreover, they also revealed difficulties in talking about their own goals and troubles in self‐management with healthcare professionals .…”
Section: Introductionmentioning
confidence: 99%
“…Autores como Navarro et al (2010) o Ahamad et al (2018) apuestan por identificar las diferencias individuales en dichas necesidades mediante una atención centrada en el paciente y desde un enfoque multidisciplinar. En la misma línea, Hillebregt et al (2017) defienden que deben identificarse aquellas necesidades críticas para cada perfil del paciente según su contexto social, sus habilidades, su estilo de vida, nivel educativo, percepciones de la enfermedad, antecedentes personales, deseos y capacidades.…”
Section: Necesidades De Información Por Parte De Los Pacientesunclassified